KEKUATAN PASAR BANK SYARIAH DI INDONESIA PERIODE 2011-2017: UNBALANCED PANEL MODEL - Devy Rahmania; Agus Suherman (Universitas Islam Syekh Yusuf, 2020)
AbstractThe aim of this research is to know the influence of efficiency towards market power, the influence of competitive condition towards market power, and the influence of efficiency and competitive condition in simultaneously toward market power of Islamic Banking in Indonesia for period 2011-2017. This research used the sample in 13 general Islamic banking. The method that used to collecting the data was secondary data of panel data which was obtained from the annual financial report data of each during observed period. The sample in this research used saturated sample where all the member of the population was used to be sample. The analysis method in this research was used unbalanced panel data regression. The result of this research showed that in partially, there was a negative and significant influence of efficiency towards market power which was indicated that if the efficiency was good thus it will reduce the average of market power rates significantly for all of the Islamic banking and otherwise. For competitive condition, the result showed that there was no significant influence of competitive condition towards market power. The value regression coefficient in competitive condition was negative, it means that if the competitive condition was increased thus it will reduce the average of market power rates significantly for all of the Islamic banking and otherwise. While in simultaneously, there was a significant influence between efficiency and competitive condition toward market power of Islamic banking in Indonesia for period 2011-2017.Keyword: Efficiency, Competitive Condition, and Market Power